Corporal Punishment in Higher Secondary Schools: A Case Study - Mondal, Nabak (JOURNAL OF INDIAN EDUCATION, 2011)
This case study was done in the district of Birbhum, West Bengal to know the status of corporal punishment in higher secondary schools. The study revealed that no teachers, parents or students in rural and urban areas are in favour of corporal punishment. A reverse relationship has been found between the parents' and teachers' attitudes towards the disciplinary actions for students in both rural and urban areas. A positive difference has been found in support of corporal punishment between the rural and urban students’ behavioural attitudes; whereas a negative difference has been found against the corporal punishment between the rural and urban students’ behavioural attitudes.